On the Desirability of Taxing Capital Income to Boost Social Insurance - Dirk Schindler; Bas Jacobs (Verein für Socialpolitik, 2010)
This paper analyzes optimal linear taxes on labor income and savings in a standard two-period life-cycle model with endogenous leisure demands in both periods and non-insurable income risks. Households are subject to skill shocks in both periods of the life-cycle. We allow for completely general skill processes including those with persistence in skill shocks. We demonstrate that capital taxes are optimal since they reduce moral hazard in social insurance in two distinct ways: i) capital taxes reduce labor supply distortions on second-period labor supply, since second-period labor supply and saving are substitutes, ii) capital taxes reduce distortions in first-period labor supply by allowing for a lower level of labor taxes, although this effect is partially off-set because first-period labor supply and saving are complements. Capital taxes will be more attractive for social insurance if a larger part of risk is realized in the first period of the life-cycle. Our results suggest that taxing (retirement) saving is optimal to boost the retirement age and to reduce the tax-burden on working-age individuals.
Keywords: H21; D80; D91; 330; Optimal Capital Taxation; Risk; Atkinson-Stiglitz theorem